Effective public-private partnership in the information technology sector : how to enhance business and trade capacities (ITC GenevaCH, 2003)
Focuses on the significance of public-private partnership in the area of information and communication technology, as a key to bridging the digital divide. Discusses the concept of partnership and describes the activities of the public/government sector in providing an overall ICT support framework. Analyzes the implication of public-private partnership for SME's and examines related experiences in the European Union and the transition economies.
Keywords: INFORMATION TECHNOLOGY